2020
DOI: 10.3390/md18070363
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia Skin Peptides Ameliorate Diabetic Nephropathy in STZ-Induced Diabetic Rats and HG-Induced GMCs by Improving Mitochondrial Dysfunction

Abstract: Diabetic nephropathy (DN) is one of the major microvascular complications of diabetes, and mitochondrial dysfunction has been observed in the kidneys of diabetic patients. Tilapia skin peptides (TSPs) are mixtures of small-molecular-weight peptides derived from tilapia skin. Rising evidence suggests that bioactive peptides from marine sources are beneficial for DN. This study aimed to investigate whether TSPs can alleviate the pathological progress in experimental DN by improving mitochondrial dysfunction thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…In 2016, approximately 18.6 million people were suffering from DFU worldwide, which seriously affects the life quality and expectancy of patients and is also a major public health problem with a heavy societal burden ( 7 ). In previous studies, it was observed that some genes were differentially expressed in DFU and control groups, which played different roles in the occurrence and development of diseases through different mechanisms of action ( 8 - 13 ). For example, rs1024611 polymorphism of the monocyte chemoattractant protein-1 ( MCP-1 ) gene is significantly correlated with MCP-1 expression and individual susceptibility to DFU ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, approximately 18.6 million people were suffering from DFU worldwide, which seriously affects the life quality and expectancy of patients and is also a major public health problem with a heavy societal burden ( 7 ). In previous studies, it was observed that some genes were differentially expressed in DFU and control groups, which played different roles in the occurrence and development of diseases through different mechanisms of action ( 8 - 13 ). For example, rs1024611 polymorphism of the monocyte chemoattractant protein-1 ( MCP-1 ) gene is significantly correlated with MCP-1 expression and individual susceptibility to DFU ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of mTOR/PINK1/Parkin-mediated mitophagy can improve renal inflammation, glomerular membrane dilatation, and extracellular matrix deposition (Wen et al, 2020). Stimulation of BNIP3/Nix signal transduction also has the same intervention effect (Jin et al, 2020).…”
Section: Mesangial Cell and Mitophagy In Dkdmentioning
confidence: 97%
“…58 In HG-induced glomerular mesangial cells, tilapia skin peptides improved mitochondrial dysfunction by upregulating Bnip3 and Nix expression and removing damaged mitochondria. 59 Importantly, Bnip3 specifically promotes the degradation of proteins in the electron transport chain without activating apoptosis, and the apoptosis-promoting effect of Bnip3 occurs when cells are severely damaged. 60 Therefore, we speculate that the downregulation of Bnip3 and Nix may cause damaged mitochondrial accumulation, leading to cardiomyocyte hypertrophy.…”
Section: Food and Function Papermentioning
confidence: 99%